Adaptive Cycle Of The Wotsogo Village Community In Facing Covid-19 Pandemic In 2020 - Diah Ainurrohmah; Rita Noviani; Yasin Yusup (Universitas Sebelas Maret, 2020)
COVID-19 is non-natural disaster that influenced in various sector of life, not only health, but also social-economic conditions, including Wotsogo Village. Therefore, it is important to conduct research related to adaptive cycle of Wotsogo Village community in facing of COVID-19. This adaptive cycle can reflect the level of community resilience which influenced by various factors. This research used descriptive qualitative method with Miles and Huberman's interactive model and scoring technique analysis. The results of the analysis show that adaptive cycle of Wotsogo Village community in facing of COVID-19 was marked by three moments distribution, were the first distribution moment of COVID-19 in Indonesia, the second moment is implementation of COVID-19 policies, and last the towards New Normal moment. The scoring results show that the level of resilience of the Wotsogo Village community was classified as moderate that spread in three RW areas and high that spread in nine RW areas.